ENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE PROBLEM SOLVING PADA MATERI POKOK LINGKARAN - Suminto, author (JURNAL E-DUMATH, 2015)
Learning Mathematics in SMP Muhammadiyah Pringsewu tends to be teacher-centered learning process. Teacher as the main source of learning, students is less involved in discovering the science of Mathematics, the result of studentsâ achievement is low. From that condition it is very crucial to apply the alternative learning using cooperative model type problem solving. The aims of research are to know the differences of average score between students in control and experimental class and to know which one is higher of mathematicsâ score between students in control and experiment class. The population of research is the students at eighth grade in even semester in SMP Muhammadiyah Pringsewu in the academic year of 2012/2013. The sample of research used cluster random sampling technique. The result of learning process is from test with 5 items of essay. The analysis of data using test of normality, test of homogeneity, those are as pre-requisite test before conducting t-test. From the result of data analysis, the average score of Mathematics in experiment class is 67.74 and control class is 58.21. The conclusions are; there is a significant difference between the average scores of Mathematics in experiment and control class. In addition, the average score of Mathematics in experiment class is higher than in control class.Keywords: Cooperative Learning Model, Problem Solving, Subject of Cyrcle